Merck and Vioxx. (A), Should the company continue to battle each of the 27,000 lawsuits filed against it? - Elias, Jaan; Hutchins, Spencer; Nagy, Andrea; Bagley, Constance E.; Rae, Douglas W. ([London] : SAGE, 2016)
Over the years, Merck & Co. built an enviable reputation not just as a paragon of the pharmaceutical industry but as one of America's most admired businesses. However, after withdrawing its blockbuster drug Vioxx in September of 2004, Merck found its reputation and its financial stability in danger. The day after the announcement, Merck's stock plunged 30% and a few analysts even wondered if Merck would be forced into bankruptcy. This study looks at the processes that Merck would need to go through before achieving stability.
Originally Published in: Elias, J., Hutchins, S., Nagy, A., Bagley, C. E., & Rae, D. W. (2008). Merck and Vioxx (A): Should the Company Continue to Battle Each of the 27,000 Lawsuits Filed Against It? 08-016. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Merck & Co; Crisis management -- Case studies; Actions and defenses -- Case studies